Diplomasi Gamelan di Australia - Aryani, Maria Indira; Nisa, Hasri Maghfirotin; Permatasari, Alfina; Pranoko, Dimas Evananda; Nasution, Calvin Alhafiz (Global and Policy Journal of International Relations, 2020)
Indonesia and Australia are two neighboring countries that has close relations, geographically and socio-politically. Diplomatic relations between the two was formally establish in 1949, but Australia has been giving constant support toward Indonesia’s independence since 1945. Despite these relations, Indonesia and Australia still has conflict and tensions on several issues. To maintain good relations and to reduce tensions, Indonesia is implementing Gamelan Diplomacy towards Australia. Gamelan Diplomacy is a representation of Indonesian culture and as a form of Indonesian Cultural Diplomacy. The main objective of this paper is to describe the implementation of Gamelan Diplomacy according to Simon Mark that consist of four elements, which are actors and government involvementa, objectives, activities, and audience. This paper is using a descriptive.Keywords: Gamelan Diplomacy, Cultural Diplomacy, Actor and Government Involvement, Objective, Activity, AudienceIndonesia dan Australia adalah dua negara tetangga yang memiliki kedekatan, baik secara geografis maupun sosial politik. Hubungan diplomatik antara kedua negara ini secara resmi telah terjalin sejak tahun 1949, tetapi dukungan bagi upaya perolehan kemerdekaan Indonesia telah diberikan oleh Australia sejak tahun 1945. Terlepas dari hubungan dan kedekatan yang telah lama terjalin, masih sering terjadi konflik dan ketegangan antara Indonesia dan Australia yang disebabkan oleh beberapa hal. Untuk menjalin hubungan baik, sekaligus meredam ketegangan, Indonesia menerapkan Diplomasi Gamelan di Australia. Diplomasi Gamelan yang dilakukan Indonesia terhadap Australia merupakan representasi dari kebudayaan Indonesia dan merupakan salah satu implementasi dari diplomasi kebudayaan. Tulisan ini bertujuan untuk mengetahui bagaimana pelaksanaan Diplomasi Gamelan Indonesia berdasarkan pemikiran Simon Mark yang diamati melalui empat elemen, yakni aktor dan keterlibatan pemerintah, tujuan, bentuk kegiatan dan audiens. Tulisan ini menggunakan metode penelitian deskriptif kualitatif dengan pengambilan data studi kepustakaan mulai tahun 2008, saat diadakan IndoFest pertama di Australia, hingga 2019.Kata Kunci: Diplomasi Gamelan, Diplomasi Budaya, Aktor dan Keterlibatan Pemerintah, Tujuan, Bentuk Kegiatan, Audiens DOI : https://doi.org/10.33005/jgp.v8i01.2176